2011
DOI: 10.1021/bm201098j
|View full text |Cite
|
Sign up to set email alerts
|

Designed Antimicrobial and Antitumor Peptides with High Selectivity

Abstract: We report a new class of cationic amphiphilic peptides with short sequences, G(IIKK)(n)I-NH(2) (n = 1-4), that can kill Gram-positive and Gram-negative bacteria as effectively as several well-known antimicrobial peptides and antibiotics. In addition, some of these peptides possess potent antitumor activities against cancer cell lines. Moreover, their hemolytic activities against human red blood cells (hRBCs) remain remarkably low even at some 10-fold bactericidal minimum inhibitory concentrations (MICs). When … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
158
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 113 publications
(169 citation statements)
references
References 37 publications
11
158
0
Order By: Relevance
“…In each case, one lysine is inserted into the hydrophobic isoleucine face, which was thought to help decrease hemolytic activity but has little impact on antibacterial activity. 27,30 The selective incorporation of Gly and Ile at the two termini in the four peptides enables us to examine how different terminal modifications affect the antibacterial and hemolytic activities of the peptide series.…”
Section: Resultsmentioning
confidence: 99%
“…In each case, one lysine is inserted into the hydrophobic isoleucine face, which was thought to help decrease hemolytic activity but has little impact on antibacterial activity. 27,30 The selective incorporation of Gly and Ile at the two termini in the four peptides enables us to examine how different terminal modifications affect the antibacterial and hemolytic activities of the peptide series.…”
Section: Resultsmentioning
confidence: 99%
“…The challenge in ACP designing lies on the improvements of their delivery to the tumors while maintaining a low profile of toxic effects. The low selectivity of some of the ACPs molecules, the high cost of production in large scale, and their low resistance to proteolytic cleavage (Hu et al, 2011) are some of the main reasons why peptides have been retained in drug development pipelines. There are also some concerns related to the use of AMPs whose sequences are close to human and natural AMPs due to a possible compromise of the human natural defense and consequently threat to public health (Chen et al, 2012).…”
Section: Perspectives and Open Questions On Anticancer Peptides Desigmentioning
confidence: 99%
“…amphiphilicity and cationicity. [22][23] Among this serial of peptides, G(IIKK) 3 I-NH 2 was found to display high selectivity between tumor cells and normal mammalian host cells following the extensive examination of peptide length, net positive charges, helicity and hydrophobicity. Our recent study has indicated that whilst deleting its terminal amino acids had little impact on their antibacterial behavior, their antitumor activity declined sharply.…”
Section: Introductionmentioning
confidence: 99%